Administrasi Kurikulum Pembelajaran Tahfidz di Pondok Pesantren Islamic Center Binbaz Yogyakarta - Sarwadi; Q. Robbaniyah; R. Lina (Jurnal Administrasi Pendidikan Indonesia, 2022)
Abstract: Memorizing the Al-Qur'an is not an easy task and matter, but with good and structured management it can help the Al-Quan memorizers in facilitating the memorization process well and quickly so that the process of memorizing 30 juz does not feel burdensome. Islamic Center Campus Bin Baz Islamic Boarding School as a new campus boarding school in 2021-2022 has been able to produce 8 (eight) hafidzhoh 30 juz, researchers want to know in depth how the management of tahfidzul Qur'an learning management at Islamic Center Campus Bin Baz Islamic Boarding School FY 2021- 2022. The research method used is quantitative research by collecting observation data, interviews and documentation. The result of the research is that the management of tahfidzul Qur'an learning uses four stages, namely planning, implementation, controlling and evaluation. The key to the success of learning tahfidzhul quran are first; detailed planning, namely preparing a standard system, preparing tahfidz coordinators, competent tahfidz facilitators, making visions, missions, daily, weekly, semiannual and annual work programs, student programs, curriculum and so on in detail and detail. Second; implementation and control, namely carrying out programs that have been determined in accordance with the results of the data placement test for memorization ability, amount of memorization, and quality of reading. Al-Quran learning activities are adjusted to predetermined targets and programs. Controlling is carried out by the tahfidz section and all study programs and academics Third: evaluation, evaluation is carried out both manually and online both daily, weekly, monthly, semiannually and annually